The relationship between salary levels and economic convergence in Kazakhstan - Turchekenova, R.A.; Zhanseitov, A.T.; Rakhimzhanova, R.A. (BUKETOV BUSINESS REVIEW, 2021)
Object: To consider how financial development affects income inequality in Kazakhstan taking into account foreign savings, economic development, education, and the functions of democracy as factors. Methods: For analyzing data and obtain accurate results, empirical models, variables, and measures, trends and descriptive statistics were applied. Results: The findings of experiment indicate that a 1 % rise in financial development (the distribution of domestic credit to the private sector) results in a 0.09 percent increase in income inequality. Table 1 illustrates the corresponding short-term estimate of 0.047. Conclusions: To sum up, research contributes to our knowledge of the relationship between amid income inequality, monetary development, and other governing elements in Kazakhstan during the change of period. The authors evaluate the impact of economic growth, financial development, foreign direct investment, education, and democracy on income alterations using the longest available time range. Besides, they demonstrate that Kazakhstan's financial growth exacerbates wealth inequality. In instantaneous, the three main points are sent for policy reasons. The financial sector must be strengthened in order to bridge the gap among the “haves” and “have-nots.”